DEVELOPMENT OF ASYNCHRONOUS BLENDED LEARNING (ABLE) SKILLS LAB WITH PEER EVALUATION IN MIDWIFERY STUDENTS - Dita Eka Mardiani; Dedi Rachmadi; Deni Kurniadi Sunjaya; Ike R Husen (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2020)
Background: Innovations in midwifery education is needed to strengthen students' skills. The Asynchronous Blended Learning (ABLE) Skills Lab model can improve student motivation, retention and skills, but the evaluation is still not optimal. One solution to overcome it by developing of the ABLE Skills Lab with Peer Evaluation model. This study aims to analyze the differences in the improvement of newborn resuscitation skills between the application of the ABLE Skills Lab model with  Trainer Evaluation and Peer Evaluation.Methods: This study used a quasy experimental  two group pre-post test design.  The participants involved in this research were 40 students of the fourth semester students of Diploma III Poltekkes Kemenkes Tasikmalaya who met the inclusion criteria. Subjects were divided into 4 learning groups that randomized into 2 research groups. Data were analyzed using inferential statistics and Rasch modelling. Results: There is no difference in the improvement of newborn resuscitation skills between the application of the ABLE Skills Lab with Trainer Evaluation model and ABLE Skills Lab with Peer Evaluation model (p=0,344). Conclusion: ABLE Skills Lab with Peer Evaluation model has the same ability with  Trainer Evaluation model in improving newborn resuscitation skills.ABLE Skills Lab with Peer Evaluation can be an alternative method when there are limited staff / instructors during the learning process without reducing the output produced. Keywords: ABLE skills lab, neonatal resuscitation skills, peer evaluation, trainer evaluation